Decade of research into the acceptability of interventions aimed at improving adolescent and youth health and social outcomes in Africa: a systematic review and evidence map - Marisa Casale; Lorraine Sherr; Chris Desmond; Lucie Cluver; Oluwaseyi Dolapo Somefun; Genevieve Haupt Ronnie (BMJ Open)
Objective Interventions aimed at improving adolescent health and social outcomes are more likely to be successful if the young people they target find them acceptable. However, no standard definitions or indicators exist to assess acceptability. Acceptability research with adolescents in low-and-middle-income countries (LMICs) is still limited and no known reviews systhesise the evidence from Africa. This paper maps and qualitatively synthesises the scope, characteristics and findings of these studies, including definitions of acceptability, methods used, the type and objectives of interventions assessed, and overall findings on adolescent acceptability.Design We conducted a systematic review of peer-reviewed studies assessing intervention acceptability with young adults (aged 10–24) in Africa, published between January 2010 and June 2020.Data sources Web of Science, Medline, PsycINFO, SociIndex, CINAHL, Africa-wide, Academic Search Complete and PubMed were searched through July 2020.Eligibility criteria for selecting studies Papers were selected based on the following inclusion criteria: if they (1) reported primary research assessing acceptability (based on the authors’ definition of the study or findings) of one or more intervention(s) with adolescents and young adults 10–24; (2) assessed acceptability of intervention(s) aimed at positively influencing one or more development outcome(s), as defined by sustainable development goal (SDG) indicators; (3) reported on research conducted in Africa; (4) were in the English Language; (5) were peer-reviewed and and (6) were published between 1 January 2010 and 30 June 2020.Data extraction and synthesis Abstracts were reviewed independently by the two first authors to determine relevance. Full text of potentially eligible studies were retrieved and independently examined by the same two authors; areas of disagreement or lack of clarity were resolved through discussion by the two authors and—where necessary—the assessment of a third author.Results 55 studies were considered eligible for inclusion in the review. Most studies were conducted in Southern Africa, of which 32 jointly in South Africa and Uganda. The majority of interventions assessed for acceptability could be classified as HIV or HPV vaccine interventions (10), E-health (10), HIV testing interventions (8), support group interventions (7) and contraceptive interventions (6). The objectives of most interventions were linked to SDG3, specifically to HIV and sexual and reproductive health. Acceptability was overall high among these published studies. 22 studies provided reasons for acceptability or lack thereof, some specific to particular types of interventions and others common across intervention types.Conclusions Our review exposes considerable scope for future acceptability research and review work. This should include extending acceptability research beyond the health (and particularly HIV) sector and to regions in Africa where this type of research is still scarce; including adolescents earlier, and potentially throughout the intervention process; further conceptualising the construct of acceptability among adolescents and beyond; and examining the relationship between acceptability and uptake.